Development of Islamic law: the application of ‘urf in halal animal slaughtering practices - Ab Rahman, Suhaimi; Ruzulan, Zulaipa; Abdul Karim, Muhammad Shahrim (Penerbit Universiti Teknologi Malaysia, 2014)
Islamic law is often misunderstood as a rigid and outdated law which is non-compatible to be exercised in this modern day. This is, however, not true due to the recognition of legal reasoning, al-ijtihad, in Islamic legal tradition where Islamic law is adaptable and flexible in line with the changing of times, places and circumstances. Halal industry, particularly the animal slaughtering practices is one of the areas that experience positive developments which lead to the emergence of new practices like stunning and mechanical slaughtering. Indeed, these practices are regarded as a new phenomenon in which there the issue was not clearly discussed in the classical literatures hence needs for further clarification on the status of Shariah legal rulings, hukm, from various sources of Islamic law including ‘urf. This paper is an attempt to discuss the development of Islamic law with special reference to the application of ‘urf in halal animal slaughtering practices. In order to achieve the objective, opinions from both classical and modern literatures are examined and analyzed in order to understand the development of Islamic law in halal industry. The findings show that ‘urf is considered as the most suitable instrument in determining the legal status of modern animal slaughtering practices since it is applicable to all kinds of situations, places and times.